Pengaruh Kualitas Layanan dan Kelengkapan Fasilitas Rumah Sakit Terhadap Keputusan Berkunjung Pasien Rawat Jalan - Wulandari, Rizka; Taufik, Ahmad; Syamsun, Arfi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to determine the effect of service quality and completeness of hospital facilities on outpatient visiting decisions. Respondents in this study amounted to 100 people. This type of research is quantitative research, analytical observational with cross-sectional data collection. Based on the results of the study indicate that service quality has a positive and significant effect on patient visiting decisions and the completeness of hospital facilities has a positive and significant effect on patient visiting decisions. And simultaneously the quality of service and hospital facilities both have a significant effect on the decision to visit patients to the hospital